Sine Inverter Controller with 8 Bit Microcontroller - Radim Kuncicky; Lacezar Licev; Michal Krumnikl; Karolina Feberova; Jakub Hendrych (Advances in Electrical and Electronic Engineering, 2016)
This article describes the design of a sine wave inverter control unit. We will define the basic principles and requirements to control and maintain a good quality of inverter's output. The solution that can achieve full 8 bit output resolution with 10 bit measurement and regulation time shorter than mains period is proposed. Furthermore, the possibilities and ways of implementing the control unit using the 8 bit microcontrollers are described, so it is possible to gain a complete understanding of this issue.